2019
DOI: 10.1001/jamanetworkopen.2019.14511
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Perspectives on Barriers to Discussing Infertility and Fertility Preservation With Young Women With Cancer

Abstract: This qualitative study uses interviews with 22 Canadian clinicians to examine the perceived barriers to discussing fertility and fertility preservation with young women with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
(73 reference statements)
1
38
0
3
Order By: Relevance
“…Multiple physicians in this study 14 expressed that they did not believe that they were qualified or knew enough about fertility preservation to have conversations about this issue. This study 14 found that often physicians attributed the responsibility of fertility counseling to other clinicians, focused on the part of the body being treated, and did not see fertility preservation as their responsibility. In these multispecialty clinics, physicians possibly deferred these conversations, assuming that colleagues would address risks, potentially allowing such conversations to be missed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Multiple physicians in this study 14 expressed that they did not believe that they were qualified or knew enough about fertility preservation to have conversations about this issue. This study 14 found that often physicians attributed the responsibility of fertility counseling to other clinicians, focused on the part of the body being treated, and did not see fertility preservation as their responsibility. In these multispecialty clinics, physicians possibly deferred these conversations, assuming that colleagues would address risks, potentially allowing such conversations to be missed.…”
Section: Discussionmentioning
confidence: 98%
“…One theory for this decreased rate of counseling in multispecialty clinics could be an unclear delineation of who is responsible for discussing the risk of infertility associated with chemotherapy. A recent qualitative study by Covelli et al 14 included 22 Canadian physicians who were interviewed regarding adherence to ASCO guidelines about fertility preservation conversations with patients. Multiple physicians in this study 14 expressed that they did not believe that they were qualified or knew enough about fertility preservation to have conversations about this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International guidelines recommend that oncologists address the possibility of future infertility with patients with newly diagnosed cancer in their reproductive years [7,13,14]. Despite these guidelines, the likelihood of discussions regarding fertility preservation, among others, is influenced by unfamiliarity with fertility preservation processes, risks, and outcomes [15]. Patients should be referred as early as possible to specialists who can offer fertility preservation (FP).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of a standardised process may produce guidelines that are not relevant for end-users or do not address their clinical needs. For example, when describing barriers to guideline implementation, clinicians highlight other clinical concerns that they prioritise in practice and for which guidance does not exist [12]. By incorporating clinician views into priority-setting and the development of key clinical questions in a standardised way, we may create more useful and implementable guidelines.…”
Section: Introductionmentioning
confidence: 99%